Progression in Diagnosis and Treatment of Resistant Hypertension - Mingjun HE; Jianjun MU; Fuqiang LIU; Keyu REN; Yang WANG; Tongshuai GUO (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2014)
Introduction: Resistant Hypertension (RH) is a major risk factor of numerous diseases. RH is a challenging clinical problem,many factors affect blood pressure (BP) control. Correct diagnosis and appropriate drug therapy are pretty important to get BP controlled. We aim to attract physicians' attention to adopt correct measures to diagnose and treat RH. Method: Articles are obtained from the Internet, www.pubmed.com, Medline and several authors via e-mail. Result and Conclusion: 1.Using a systematic approach to find out the causes of RH and the distinctions between pseudo-resistance and true resistance areof importance for treatment. 2. Following the current treatment guidelines and using the standardized way to establish a flowchart to manage the patientsare the correct methods for BP control. 3. In the absence of novel antihypertensive drugs targeting new pathways, device-based therapies including RDN, carotid baroreflex activation and continuous positive airway pressure (CPAP) have shown encouraging results.4. Further efforts on the pathophysiology of RH will help to establish better drug combinations or new ways on BP control.